Title: Eskimo, Miffy, Red Riding Hood Title Vads Collection: Design Council Slide Collection - Designer: Bruna, Dick Manufacturer: Peggy Nisbet Ltd (1970)
Description: Three rag dolls designed by Dick Bruna and made by Peggy Nisbet Ltd., 1970, (from left to right): 'Red Riding Hood', 'Miffy' and 'Eskimo'.